Kemampuan Penyerapan Hara Pada Berbagai Varietas Padi Dan Sistem Pengairan Di Kabupaten Deli Serdang - Rizal Aziz (Universitas Medan Area, 2023)
This journal contains research that aims to determine the ability of rice plant tissues in several varieties to absorb nutrients in the soil and in various irrigation systems in Deli Serdang Regency. This study used an Randomized Block Design (RAKL) with the first factor consisting of 2 levels, namely P1 (intermittent irrigation method) and P2 (continuous irrigation method). The second factor consisted of 4 varieties, namely Mentik Wangi, IR-64, Segara Anak, and Cianjur. The data from the analysis showed that the Cianjur variety Ca nutrient absorption and plant dry weight at the 13th week was influenced by various rice varieties and irrigation types, compared to other varieties. The conventional irrigation system showed Ca uptake and plant dry weight 13 weeks higher than SRI irrigation.